(untitled) (REMUNOM, 2024)
Abstract: Evolution is considered as the guiding axis of biology by most authors because it is a theory of great explanatory power, therefore, its teaching becomes essential for students to have an absolute understanding of evolutionary concepts. Proposing alternatives for the improvement of science education with the use of comic strip and, so that basic knowledge, science knowledge is integrated in an integrated way with evolutionary concepts; This research aims to investigate knowledge about evolutionary concepts, carried out by a graduate student in Biological Sciences during Science classes. The research, of quantitative and exploratory type, used as a data source a closed questionnaire, with sixteen questions with four answer options and applied to students in three classes of seventh grade of elementary school in two school units, one in municipal network and another in the state network, in the State of Rio de Janeiro. The results obtained numerically were converted into percentages and transformed into graphs prepared using the GraphPad Prism 8.0 program. The answers obtained in the questionnaire were separated into four categories based on concepts worked on. Among the school units there were differences in the understanding of the concepts worked on. Due to the conceptual doubts pertinent to the students’ age group, it is noted that the comic books bring a motivation that allows them to better understand natural selection and the concepts involved, demonstrating that it is essential to approach evolutionary theory with didactic resources.